Mieczysław Broniatowski – meandry kariery „dąbrowszczaka” w PRL - Lesiakowski, Krzysztof (Przegląd Nauk Historycznych, 2015)
Communist machinery of state, which was formed in Polish territory since 1944, needed numerous amount of workers. One of the sources of them were participants who took a part in the Spanish Civil War in 1936-1939. In this situation it was predictable that in the post-war Poland participants of XIII ‘Jarosław Dąbrowski’ International Brigade, would be nominated for main offices in different institutions. This problem was analyzed mostly on a base of col. Mieczysław Broniatowski history – one of near 4 thousands of ‘dąbrowszacy’. In conclusion it occurred that ‘dąbrowszczacy’ played symbolic role, rather than group of pressure in PRL. In times of crisis they often were in different camps. Despite the fact that they were surrounded by a nimbus of heroes of the war in Spanish, they didn’t exercise main functions. On this background, it can be said that Broniatowski’s career wasn’t specially different from experiences of his comrades from ‘dąbrowszczacy’. He quickly became one of new regime creators, however he didn’t managed to came to the top.